2006
DOI: 10.1002/uog.3821
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of sacrococcygeal teratoma associated with acute fetal anemia

Abstract: Sacrococcygeal teratoma (SCT) is the most common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
19
0
2
Order By: Relevance
“…Baschat and associates have detected increased MCAPSV in a case of severe acute FMH, confirmed by the Kleihauer-Betke test (19). In a later study, Yamaguchi and associates demonstrated increased PSV of MCA in an actively bleeding fetus due to spontaneous rupture of a sacrococcygeal teratoma (20). To the best of our knowledge, no study has previously investigated the effect of transplacental bleeding on MCAPSV.…”
Section: Discussionmentioning
confidence: 86%
“…Baschat and associates have detected increased MCAPSV in a case of severe acute FMH, confirmed by the Kleihauer-Betke test (19). In a later study, Yamaguchi and associates demonstrated increased PSV of MCA in an actively bleeding fetus due to spontaneous rupture of a sacrococcygeal teratoma (20). To the best of our knowledge, no study has previously investigated the effect of transplacental bleeding on MCAPSV.…”
Section: Discussionmentioning
confidence: 86%
“…The Ibele approach reports observation of the fetus with serial ultrasound and intervention before the development of fetal hydrops as heralded by fetal abdominal ascites, scalp edema, worsening placentomegaly, and anemia [14]. They follow middle cerebral artery peak systolic velocity, which has been shown to be a good parameter for the evaluation of fetal anemia [20][21][22] diagnosing moderate and severe anemia in fetuses with a sensitivity of 100% [20,22]. A publication from the University of California at San Francisco in 2011 by Byrne et al [23] presented outcomes based on specific ultrasonographic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Without cardiac compromise or hydrops, 88% survival is quoted [111]. Perinatal mortality results from tumour avulsion, rupture or haemorrhage at delivery [112,113]. With cardiac compromise or hydrops mortality approaches 100% [111].…”
Section: Sacrococcygeal Teratomamentioning
confidence: 99%